Analysis of complications after living-related kidney transplantation: a single-center experience - F. A. Khadjibaev; V. Kh. Sharipova; P. K. Sultanov (Трансплантология (Москва))
Background. The one-year renal graft survival rates have grown to 93.4% for transplantation from cadaveric and 97.2% from living donors. Early detection and elimination of complications after kidney transplantation improve these figures.The study purpose was to develop an algorithm for the diagnosis and treatment tactics of postoperative complications after kidney transplantation by reviewing literature data and analyzing the results of our own experience.Material and methods. The study included 75 patients who underwent kidney transplantation from a living donor at the Republican Research Centre of Emergency Medicine from March 2018 to December 2019.Results. The original authors' algorithm developed for the diagnosis and treatment of complications after kidney transplantation covers all postoperative complications that lead to renal transplant dysfunction. It is based on assessing the symptoms that typically occur in a specific complication. The main instrumental methods in the diagnosis of postoperative complications are ultrasound and radiological investigational techniques. The biopsy has the main role in diagnosing a graft rejection. Among 75 patients after kidney transplantation, 23 (30.6%) developed various early postoperative complications, including both surgical and immunological ones. Renal graft dysfunction was eliminated in 17 (73.9%) of 23 patients. The loss of a transplanted kidney was associated with the death of 7 recipients (9.3%). The causes of death were pulmonary embolism in 2 (2.7%) cases, infection and sepsis as a result of immunosuppression in 2 (2.7%) cases, hypovolemic shock in 2 (2.7%) cases, and acute ischemic stroke in 1 (1.3%) case. Two recipients underwent renal transplant nephrectomy. The cause of nephrectomy was graft rejection and bleeding from the renal artery. A oneyear survival rate was 90.7%. The proposed treatment and diagnostic algorithm showed a 95.7% diagnostic value in identifying the complications, and 91.3% of the therapeutic effect in coping with a renal transplant dysfunction.Conclusions. Early treatment of revealed complications allows saving the transplanted kidney function. Step-bystep differential diagnosis of complications after kidney transplantation, according to the proposed algorithm, allows choosing the treatment tactics based on complication pathogenesis.